EFFECT OF BEHAVIOURAL CHANGE COMMUNICATION ON FEMALE MENIAL WORKERS’ UTILISATION OF BREAST CANCER SCREENING IN OYO AND OSUN STATES, NIGERIA (2017)
Early detection through screening has been acclaimed to be the antidote for preventing breast cancer related morbidity and mortality among women. Regardless of its significance, there exist poor knowledge and negative attitude towards breast screening, particularly among low socio-economic status women. However, this trend can be changed through behavioural communication interventions. Previous studies focused largely on the use of the mass media, despite its inherent weaknesses to bring about desired change in health behaviour. This study, therefore, examined the effect of Behavioural Change Communication (BCC) on female menial workers’ utilisation of breast cancer screening in Oyo and Osun states, Nigeria. The moderating effects of age and educational attainment were also determined. The study was anchored on Health belief model, Diffusion of Innovation, and Planned behaviour theories, while the pretest-posttest control group, quasi-experimental design of 2x3x2 factorial matrix was adopted. One private and public university each with Teaching hospital that has a breast cancer unit was purposively selected from the two states. Female menial workers’ who are outsourced staff of the two universities were selected. The participants were randomised into BCC (50) and Control (50) groups, while treatment lasted eight weeks. Instruments used were Breast Cancer Disease Awareness Scale (r=0.80) Breast Cancer Screening Questionnaire with four subscales (Knowledge/Awareness- r=0.71, Sources of Information- r=0.85, Screening Method- r=0.91 and Utilisation - r=0.72), and BCC and control packages and guides. Data were subjected to percentages and Analysis of Co-variance and Duncan posthoc test at 0.05 level of significance. Participants were mainly married women (98.0%) aged between 20 and 50+ years; with educational attainment of elementary (64.0%) and secondary (32.0%). Knowledge about breast cancer before the intervention was 14.0% and 99.8% after the intervention, while the source of their information about breast cancer was solely from print and electronic media. There was a significant main effect of treatment on female menial university workers’ utilisation of breast cancer screening in Oyo and Osun states (F(1, 91)=72.16, ŋ2=.42). Participants in BCC had a higher post treatment mean score of 48.70 than those in the control group ( =30.22). There was a significant main effect of educational attainment on female menial university workers’ utilisation of breast cancer screening (F(1, 91)=22.06, ŋ2=.32); while age had none. Participants with high educational attainment had higher breast screening utilisation ( =40.92) than those with low educational attainment ( =38.12). There were no significant two-way interaction effects of treatment and age, treatment and educational attainment, and age and educational attainment on breast cancer screening utilisation. The three-way interaction effect was not significant. Behavioural change communication was effective in creating awareness and fostering utilisation of breast cancer screening among female menial university workers’ in Oyo and Osun states, Nigeria. Education was a determining factor in the adoption of breast cancer screening. Therefore, women, particularly those with low educational attainments should be well exposed to behavioural communication interventions to create and sustain awareness to enhance adoption of breast cancer screening.